ANALISIS KEMAMPUAN GURU IPA SMP DI KOTA PEKANBARU DALAM MELAKSANAKAN ASESMEN AUTENTIK TAHUN PELAJARAN 2015/2016 - Endang febrianti; Dra.Mariani Natalina.L.,M.Pd; Dra. Sri Wulandari, Msi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of the study is to know the ability of teachers IPA SMP in Pekanbaru Implementing Authentic Assessment Year 2015/2016 ". The rescarch conducted in March to June 2016. The sample in the rescarch is 21 teachers IPA SMP in Pekanbaru. The collection data instrument use a questionnaire enclosed, open questionnaire and analyze the assessments made by the teachers IPA SMP in Pekanbaru. Closed questionnaire consists of 26 statements that the divided into three indicators: planning, execution, and reporting and 27 questions ions about the comprehension of assessment authentic that divided into four indicators that (knowledge assessment authentic learning, cognitive, affective domain, domain psychomotor), and on the teacher, IPA SMP in Pekanbaru , collected as many 1 teacher of every 6 school. The image understanding of teachers junior IPA SMP in Pekanbaru in the assessment authentic obtained as follows: planning indicate the criteria very well with average 4:50, Execution show sufficient criteria with average 3:35 and reporting showed sufficient criteria with a mean of 3.40 competency knowledge with the criteria very less with the average 55% attitude competencies are in less criteria with an average of 69% while the skill competencies are at once less criteria with an average 37%, while the comprehension of authentic assessment also showed sufficient criteria with the average percentage of 67.35%.Key Words: Analysis, the ability of teachers, authentic assessment, a science teacher